Analisa Metode Forward Chaining Untuk Sistem Pakar Pembagian Harta Warisan Sesuai Hukum Islam - Nadya Andhika Putri; Subhan Hartanto (INTECOMS: Journal of Information Technology and Computer Science, 2020)
The amount of the value of inherited property that can be divided is when the estate after deducting the amount of the testator if there pewasiat, accounts payable and cost of the management body. The result of the division is in the form of a percentage value to each of the heirs entitled to the estate setelahdilakukan processing division. Users system this expert to be able to obtain the nominal value of the treasure division by multiplying the percentage the division with the overall value of the estate. The results obtained from this expert system in the form of output information the class of heirs entitled to receive the inheritance, and if the value of the percentage of the opinion of the inheritance for each heir is entitled to get the treasure, inheritance